Chromium Recovery from Chromium-Loaded Cupressus lusitanica Bark in Two-Stage Desorption Processes - Alma Rosa Netzahuatl-Muñoz; Erick Aranda-García; Eliseo Cristiani-Urbina (Plants, 2023)
Hexavalent chromium (Cr(VI)) contamination poses serious health and environmental risks. Chromium biosorption has been employed as an effective means of eradicating Cr(VI) contamination. However, research on chromium desorption from chromium-loaded biosorbents is scarce despite its importance in facilitating industrial-scale chromium biosorption. In this study, single- and two-stage chromium desorption from chromium-loaded Cupressus lusitanica bark (CLB) was conducted. Thirty eluent solutions were evaluated first; the highest single-stage chromium desorption efficiencies were achieved when eluent solutions of 0.5 M NaOH, 0.5 M H2SO4, and 0.5 M H2C2O4 were used. Subsequently, two-stage kinetic studies of chromium desorption were performed. The results revealed that using 0.5 M NaOH solution in the first stage and 0.5 M H2C2O4 in the second stage enabled the recovery of almost all the chromium initially bound to CLB (desorption efficiency = 95.9–96.1%) within long (168 h) and short (3 h) desorption periods at each stage. This study clearly demonstrated that the oxidation state of the recovered chromium depends on the chemical nature and concentration of the eluent solution. The results suggest the possible regeneration of chromium-loaded CLB for its subsequent use in other biosorption/desorption cycles.